1990
DOI: 10.1136/bmj.301.6765.1391
|View full text |Cite
|
Sign up to set email alerts
|

Congenital rubella in the Asian community in Britain.

Abstract: for those relating to issues discussed recently (within six weeks) in the BMJ. * We do not routinely acknowledge letters. Please send a stamped addressed envelope ifyou would like an acknowledgment.* Because we receive many more letters than we can publish we may shorten those we do print, particularly when we receive several on the same subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…20 It has also been reported in previous British studies that a high proportion of children with congenital rubella have mothers of Asian background 8 , and that women who are from a minority ethnic background are more likely than white British women to be seronegative to rubella. 7,9 The use of data linkage in this study allows us to estimate the prevalence of rubella susceptibility in pregnant women by country of birth thus reflecting the effect of different immunization policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has also been reported in previous British studies that a high proportion of children with congenital rubella have mothers of Asian background 8 , and that women who are from a minority ethnic background are more likely than white British women to be seronegative to rubella. 7,9 The use of data linkage in this study allows us to estimate the prevalence of rubella susceptibility in pregnant women by country of birth thus reflecting the effect of different immunization policies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of rubella immunity during pregnancy have shown that in the UK women from minority ethnic groups are more likely to have low or undetectable rubella antibody levels than those from other groups. 79…”
Section: Introductionmentioning
confidence: 99%